Assessment of Islamic E-Business Transactions in Small and Medium-sized Enterprises (SMEs) and their Impact on Muslims in Northwestern Nigeria - ISA, Abubakar Dutsin-Amare; Muhammad Gusau Ahmad; Ibrahim Shuaibu Sai’d; Gambo Rafindadi Ibrahim; Adamu Abubakar Muhammad (Indonesian Journal for Islamic Studies, 2025)
The study evaluates the dynamics of Islamic e-business transactions in Small and Medium-sized Enterprises (SMEs) and their socio-economic impact on Muslims in Northwestern Nigeria. By examining the integration of Sharˉiʽah -compliant principles within digital commerce, the research explores how Islamic jurisprudence influences online business practices, including contract fairness, transparency, and prohibition of interest (riba). A mixed-methods approach involving surveys, interviews, and content analysis was employed to assess the awareness, adoption, and challenges faced by Muslim entrepreneurs and consumers. Findings reveal a growing acceptance of Islamic e-business models, driven by the need for ethical commerce, though constrained by limited digital literacy and infrastructural deficits. Quantitative and qualitative analysis reveals that adherence to Islamic principles such as the avoidance of usury and haram products varies among MSMEs. The lack of knowledge on Islamic finance among MSME owners highlights the need for training and awareness campaigns. Consumer trust in halal-certified platforms and Islamic payment gateways is generally positive, although fraud and regulatory concerns remain. Statistical analysis shows a strong correlation between MSME performance and adherence to Islamic business ethics. MSMEs using Islamic financial instruments such as Murabaha and Mudaraba show improved financial stability and market expansion. The interview results confirm the importance of regulatory intervention to create an enabling environment for Shariah-compliant e-businesses. The paper concludes with recommendations to enhance Islamic e-business adoption, highlighting its potential to boost financial inclusion and economic empowerment among Muslims in the region while preserving religious values.